Ambient Synthesis of Single‐Atom Catalysts from Bulk Metal via Trapping of Atoms by Surface Dangling Bonds. Issue 44 (11th September 2019) - Qu, Yunteng; Wang, Liguang; Li, Zhijun; Li, Peng; Zhang, Qinghua; Lin, Yue; Zhou, Fangyao; Wang, Huijuan; Yang, Zhengkun; Hu, Yidong; Zhu, Mengzhao; Zhao, Xuyan; et al.
Abstract: Single‐atom catalysts (SACs) feature the maximum atom economy and superior performance for various catalysis fields, attracting tremendous attention in materials science. However, conventional synthesis of SACs involves high energy consumption at high temperature, complicated procedures, a massive waste of metal species, and poor yields, greatly impeding their development. Herein, a facile dangling bond trapping strategy to construct SACs under ambient conditions from easily accessible bulk metals (such as Fe, Co, Ni, and Cu) is presented. When mixing graphene oxide (GO) slurry with metal foam and drying in ambient conditions, the M 0 would transfer electrons to the dangling oxygen groups on GO, obtaining M δ+ (0 < δ < 3) species. Meanwhile, M δ+ coordinates with the surface oxygen dangling bonds of GO to form MO bonds. Subsequently, the metal atoms are pulled out of the metal foam by the MO bonds under the assistance of sonication to give M SAs/GO materials. This synthesis at room temperature from bulk metals provides a versatile platform for facile and low‐cost fabrication of SACs, crucial for their mass production and practical application in diverse industrial reactions. Abstract : A facile dangling bond trapping strategy to construct single‐atom catalysts (SACs) under ambient conditions from easily accessible bulk metals (such as Fe, Co, Ni, and Cu) is presented. This synthesis at room temperature from bulk metals provides a versatile platform for facile and low‐cost fabrication of SACs, crucial for their mass production and practical application in diverse industrial reactions.